The Analysis of Strategic Role of Student Association in Improving Discipline Attitude and Forming Quality of Graduates - Firman Ashadi; Dasep Supriatna; Muhammad Haris; Uswatun Hasanah; Ahmad HinayatulohI (Journal on Education, 2023)
The purpose of this research is to obtain data about the process of intra-school student organization activities. The spirit of discipline between administrators and members of intra-school student organizations; what are the obstacles to the implementation of the intra-school student organization program; efforts to increase discipline in intra-school student organizations; and how to overcome discipline and achieve student achievement. The method used in this research is a qualitative approach through stages of observation, interviews, and documentation studies. The objects of this study were the principal, the deputy head of student affairs, members of intra-school student organizations, and 10 students. Data analysis can be done through categorization, data reduction, validity testing, drawing conclusions, and data presentation. The results of the study show that intra-school organization activities play an important role in improving discipline and the quality of graduates through intra-school student organization work programs contained in the intra-school student organization structure and student achievement data.